Scientometric Analysis of Urban Studies Challenges and Crises with an Emphasis on Creative Approaches in Urban Management - Akbarpourganje, Atiye; Behzadfar, Mostafa; Daneshpour, Seyed Abdolhadi (Management Strategies and Engineering Sciences, 2023)
A precise understanding of the conceptual differences between urban challenges and crises not only aids in identifying research and executive priorities in urban studies but also serves as a foundation for developing innovative strategies for managing these issues. This study aims to conduct a scientometric analysis of urban challenges and crises and examine the potential of creative approaches in managing these issues. To this end, research indexed in the Scopus citation database was analyzed using co-occurrence network analysis of keywords, and research patterns, geographical distribution, and thematic trends were examined. Findings indicate that housing, sustainability, and climate change are among the most frequently cited urban challenges, while topics such as smart cities, resilience, gentrification, and informal settlements have gained increased attention in recent years. On the other hand, housing, economic, and financial crises have been identified as the most significant urban crises in the scientific literature. The thematic distribution analysis of urban challenges research highlights significant differences in research priorities across countries, where developed countries predominantly focus on long-term and sustainable challenges, whereas developing countries face more immediate and livelihood-related crises. Furthermore, the limited focus of research on urban crises on specific issues underscores the need for a global commitment to controlling and managing these crises. This study emphasizes the necessity of leveraging creative approaches in managing urban challenges and crises and highlights the potential of the creative city as a framework for developing innovative solutions and flexible responses to complex urban issues.